Low-Dose Melittin Enhanced Pigment Production Through the Upregulation of Tyrosinase Activity and Dendricity in Melanocytes by Limiting Oxidative Stress: A Therapeutic Implication for Vitiligo - Manoj Kumar Tembhre; Shipra (Antioxidants)
Melittin is a major active ingredient of the bee venom produced by honeybees (Apis mellifera) that exerts various biological effects, such as anti-inflammatory, anti-tumor, anti-microbial, and antioxidant. The role of melittin in modulating melanin production by melanocytes is not known. Therefore, the present study aimed to study the effect of melittin on melanin production by human melanocytes along with its antioxidant status. Cultured human melanocytes were treated with melittin in a dose- and time-dependent manner, followed by the study of the cell viability, cell proliferation, and total melanin content. The effects of melittin in combination with narrow-band ultraviolet B (NB-UVB) on the total melanin content, melanocyte dendricity, oxidative stress, and the expression of genes associated with melanogenesis were investigated. An increased melanin content was observed with a low dose of melittin (LDM) (alone or in combination with NB-UVB), and there was a corresponding increase in the tyrosinase activity, melanocyte dendricity, and melanogenesis-associated genes. The present study concluded that LDM alone or LDM (+NB-UVB) can induce melanin synthesis by increasing the tyrosinase activity in melanocytes by limiting the oxidative stress, and this may be therapeutically exploited as an adjuvant therapy for vitiligo.